Pengaruh Corporate Social Responsibility Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderating ( Studi Kasus Bank UMUM Syariah Indonesia ) - Ananda Ibnu Sobri Hsb; Mustafa Khamal Rokan; Nursantri Yanti (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This research aims to find out and analyze how and how much influence individual factors and social factors have on students' interest in pursuing a career in sharia banking. The research method used in this research is a quantitative descriptive approach. The type of data used is secondary data obtained from the BEI. The subject of the research is a Sharia Commercial Bank and the object of this research is 5 years. The test tool used in this research is Eviws 20.0 to test classical assumptions, multiple regression analysis, and hypothesis testing. Based on the results of hypothesis testing, namely Corporate Social Responsibility and Managerial Ownership of Company Value. So the research hypothesis testing is that Ha is accepted and H0 is rejected. Based on the results of hypothesis testing, namely Corporate Social Responsibility and Managerial Ownership of Company Value with Profitability as moderation. So the research hypothesis testing is that Ha is accepted and H0 is rejected